Estudo do Envolvimento da Bioactivação Metabólica no Efeito Hiponatrémico da 3,4 - Metilenodioximetanfetamina (Ecstasy) - Silva, Daniel Gomes Esteves da (2007)
Although considered as safe drugs by many, exaggerated responses and deaths have been reported due to 3,4-methylenedioxymethamphetamine (MDMA; ecstasy) abuse. One of the adverse effects associated with ecstasy intoxications is hyponatremia that has been related with a disruption on the release of the antidiuretic hormone (ADH or arginine-vasopressin) and pointed out as the possible cause of numerous severe and fatal intoxications after intake of this drug. Recent in vivo studies with human healthy volunteers and also in vitro studies performed with rat isolated hypothalamus have shown that the metabolic bioactivation of MDMA, namely its demethylenation followed by O-methylation of the resulting cathecol metabolite are crucial for the release of ADH both in vivo and in vitro. For the evaluation of the contribution of this metabolic pathway to the in vivo expression of the hyponatremic effect of MDMA it is crucial to quantify these metabolites, and to relate the metabolic profile with the magnitude of the hyponatremic effect. For this purpose, a GC-MS/MS method was developed to quantify MDMA and its main metabolites: methylenedioxyamphetamine (MDA), 4-hydroxy-3- methoxyamphetamine (HMA) and 4-hydroxy-3-methoxymethamphetamine (HMMA), in plasma and urine. To better understand the influence of MDMA and its metabolic bioactivation in the secretion of AVP in vivo studies were performed with male and female Wistar rats, the MDMA dose tested was 20 mg/kg. In the studies preformed 1 hour after the MDMA administration the plasmatic levels of AVP and the plasmatic concentrations of MDMA, MDA, HMA and HMMA were evaluated. The plasmatic concentrations of AVP obtained with the treated animals were compared with the concentrations obtained with the controls showing a statistically significant increase of AVP levels in the animals treated with MDMA. Correlations between the MDMA, MDA, HMA and HMMA and the AVP plasmatic levels were also preformed. No significant correletions were obtained. In the studies preformed 24 hours after the administration of MDMA the urinary and plasmatic levels of AVP were evaluated. The concentration of MDMA, MDA, HMA and HMMA were determined in plasma and urine. It was also established the ratio between the volume of ingested water and the volume of excreted urine. The plasmatic and urinary AVP concentrations obtained in the treated animals were compared with the concentrations obtained from the controls. This compairison showed significant increases of the urinary AVP levels in the treated animals. The evaluation of the correlations between the urinary concentrations of AVP and the urinary concentrations of MDMA, MDA, HMA and HMMA showed significant correlations between AVP and MDMA, MDA, HMA and HMMA. The evaluation of the ratio between the volume of ingested water and the volume of excreted urine showed that the treated animals excreted less urine in comparison with the ingested water. The studies performed with urines collected 24 hours after MDMA administration have shown significant positive correlations between AVP and the concentrations of MDMA, MDA, HMA and HMMA. The strongest correlation was established between the concentrations of HMMA and AVP. With this study it was possible to confirm the in vivo changes in the AVP secretion profile and relate those changes with the levels of MDMA, MDA, HMA and HMMA. It was also shown for the first time the induction of the secretion of AVP in male and female rats, one hour after the administration of MDMA. The consequent antidiuretic effect can be related with the hiponatremic effect.